HYDROLOGY ANALYSIS FOR THE JOHOR RIVER USING SYNTHETIC UNIT HYDROGRAPH GAMA I - Dyah Indriana Kusumastuti (UNIVERSITAS LAMPUNG, 2009)
A series of floods occurred in several places in Malaysia during December 2006 – January 2007,including the southern state of Malaysia; Johor Bahru. The rain recorded in the city of JohorBahru was 286 mm. To understand this phenomenon and to investigate the design flood of thisregion, a hydrology analysis procedure was taken into account. The hydrology analysis procedureincludes collecting rainfall data, analyzing rainfall data including areal rainfall and rainfallfrequency, developing synthetic unit hydrograph using SUH GAMA I. It is noticed that the lengthof rainfall data collected, i.e. 60 years, is sufficiently long for analysis. From the hydrologyanalysis done in this study, it can be concluded that the rain fell during 2006-2007 flood eventshad nearly 100 years period of rainfall. And the prediction for 100 years period of flood is 16,962m3/s.